A bi-functional Co–Ni layered double hydroxide three-dimensional porous array electrode derived from ZIF-L(Co)@ZIF-L(Co, Ni) for oxygen evolution reaction and supercapacitors. (19th April 2022) - Chen, Chao; Deng, Xiaohua; Deng, Yingjie; An, Lu; Deng, Yijie; Zheng, Yuying; Dang, Dai; Yang, Xu
Abstract: Developing high-efficiency bifunctional materials for electro-catalysis and supercapacitors are urgently needed but challenging. Herein, we develop a self-supporting Co–Ni LDH electrode prepared by in-situ growing ZIF-L(Co)@ZIF-L(Co, Ni) on carbon paper followed by a pseudomorphic transformation. The optimized Co–Ni LDH/carbon paper electrodes (CN-2/CP) exhibit excellent electrochemical activity and stability in oxygen evolution reactions (OER) and supercapacitors. The CN-2/CP electrode displays a low overpotential of 230 mV at 10 mA cm −2 and superior stability at 40-h chronopotentiometry for OER. For supercapacitor, the CN-2/CP electrode delivers a high specific capacitance of 1346 F g −1 at 1 A g −1 and maintains a capacitance of 88.5% after 7000 charge/discharge cycles at 20 A g −1 . Based on the physical and chemical characterization results, the high performance originates from the in-situ electrochemical conversion of metal hydroxide, improved conductivity, fast charge transfer at the interface and unique layered cross morphology providing more active sites. Graphical abstract: Image 1 Highlights: In-situ synthesis of Co–Ni LDH 3D porous array on carbon paper. The self-supported electrode exhibits high OER performance and stability. The large surface area and high porosity of CoNi LDH provide abundant active sites.